A categorial study of initiality in uniform topology - Brümmer, Guillaume C L (Department of Mathematics and Applied Mathematics, 2016)
This thesis consists of two chapters, of which the first presents a categorial study of the concept of initiality (also known as projective generation) and the second gives applications in the theory of uniform and quasi-uniform spaces.